Respostas

A melhor resposta!
2014-06-17T18:58:18-03:00
 x^{2} +6x+ y^{2} +y=-33/4

É necessário converter essa equação para sua forma reduzida, tal qual: (x-a)^{2} + (y-b)^{2} = R^{2}

Onde:  \left \{ {{(a,b)=>centro} \atop {R=>raio}} \right.

x^{2} +6x+ 9-9+y^{2} +y+ \frac{1}{4} - \frac{1}{4} =-33/4

 (x+3)^{2} + (x+ \frac{1}{2} )^{2} - \frac{37}{4} =- \frac{33}{4}

 (x+3)^{2} + (x+ \frac{1}{2} )^{2} = \frac{37}{4} - \frac{33}{4}

 (x+3)^{2} + (x+ \frac{1}{2} )^{2} = \frac{37-33}{4}

 (x+3)^{2} + (x+ \frac{1}{2} )^{2} = \frac{4}{4}

 (x+3)^{2} + (x+ \frac{1}{2} )^{2} =1

Centro → (-3,- \frac{1}{2} )

Raio → 1

3 5 3